Role of women on prevention of agrochemical poisoning in a farming community in the Tissamaharama divisional director of health services area - Dissanayaka, W.C.W.M (My University, 2004)
It was found that the majority of women had satisfactory knowledge on agrochemical poisoning. They also had a fair knowledge on first aid measures that should be practiced following exposure to agrochemicals. significant percentage of children aged 10 - 14 years were engaged in agricultural activities including handling agrochemicals. Women’s knowledge should be further improved on common symptoms of agrochemical poisoning, adverse health effects of misuse of agrochemicals and important first aid measures through awareness programmes. Usage of agrochemicals by children should be discouraged as much as possible and they should b-e educated about agrochemical poisoning and protective measures through seminars and workshops in schools. The use of pesticide traders in this process seems to be practicable. Women can motivate their family members to use protective measures and they can act as change agents to prevent misuse of agrochemicals. Public Health Midwives could assist in this process. Women should be provided with more information and training on protective measures, minimal usage of agrochemicals and organic farming. With the help of agrochemical industry should make available low coast, good quality protective equipments and carry out awareness programme on usefulness of those. Such progammes and applicants should be supervised